PENERAPAN MEDIA PEMBELAJARAN PREZI DALAM MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS X SMAN 1 SEMPARUK - Saputra, Eko; Noor, Agus Sastrawan; Sumartono, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is the application of the Prezi learning media in increasing the learning activities of students of class X SMA Negeri 1 Semparuk. This study intend to determine the application of prezi learning media in increasing student learning activities in economic subjects class X at SMA Negeri 1 Semparuk. The research method used is an experimental method with a form of pre-experimental the research design in this study is One-Group Pretest-Posttest Design. The source of the data in this study was students of class X B students in SMA Negeri 1 Semparuk. The process of determining the class to be the sample of this study is based on the average daily test scores of class X, and class X B has the lowest average value. The results showed the average student learning activities before using the prezi learning media was 69.50 while the average learning activities after using the prezi learning media became 75.72 so that there was an increase in student learning activities by 6.22. The tools of data collecting is used consist of observation and documentation study. Based on data analysis used using the t-test (Î± = 5%), the significance value was 0,000. This shows that the application of prezi learning media can increase learning activities in economic subjects in class X in SMA Negeri 1 Semparuk.Â Keywords: Prezi learning media, Learning activity